Plunder ebook A memoir of family property and nazi treasure. - Kaiser, Menachem (2024)
A New York Times Critics’ Best Nonfiction Book of 2021 Canadian Jewish Literary Award for Biography From a gifted young writer, the story of his quest to reclaim his family’s apartment building in Poland—and of the astonishing entanglement with Nazi treasure hunters that follows  Menachem Kaiser’s brilliantly told story, woven from improbable events and profound revelations, is set in motion when the author takes up his Holocaust-survivor grandfather’s former battle to reclaim the family’s apartment building in Sosnowiec, Poland. Soon, he is on a circuitous path to encounters with the long-time residents of the building, and with a Polish lawyer known as “The Killer.”  A surprise discovery—that his grandfather’s cousin not only survived the war, but wrote a secret memoir while a slave laborer in a vast, secret Nazi tunnel complex—leads to Kaiser being adopted as a virtual celebrity by a band of Silesian treasure seekers who revere the memoir as the indispensable guidebook to Nazi plunder. Propelled by rich original research, Kaiser immerses readers in profound questions that reach far beyond his personal quest. What does it mean to seize your own legacy? Can reclaimed property repair rifts among the living?  Plunder  is both a deeply immersive adventure story and an irreverent, daring interrogation of inheritance—material, spiritual, familial, and emotional.